An analytical study of reality of the proces of selecting students and directing them towords sports clubs - chikh almahdi, (sports creativity, 2025)
it The study aimed to find An analytical study of reality of the prosces of selecting stude to reach them to the highest levels, and this for the purpose of relying on them in the future, which requires a good selection in all respects, but must We note before this selection that there are some measurements and specifications that the pupil must pass to be eligible to continue participating in the school clubs and then directing them towards the sports clubs without leaving room for chance in this choice, because the process is complicated and needs a work programmed on scientific basis By specialists, these principles are the physical, morphological and psychological standards and the extent to which they are applied in the process of selection and guidance, which is the focus of our study, in which we used the descriptive and analytical method suitability with the nature of the study and the questionnaire was used as a tool for data collection and may The researcher reached all the partial hypotheses which indicated the adoption of physical, morphological and psychological criteria in the process of selecting pupils in school sports and then directing them towards sports clubs